Analyzing Students’ Achievement for Informing Educational Policy Development in Nepal - Acharya , Milan; Timilsina , Suresh (Educational Journal, 2024)
Using a quantitative research design, this study examines the level of students’ accomplishment in Nepalese schools and compares school-level achievement to the national average. The study studies students’ diversity factors such as gender, province, ecological zone, and the effect of bullying on academic achievement. To guarantee national representative, schools were chosen from every province in the Federal Nepal using a multi-stage sampling technique. The results show that the average achievement score is 43, which is lower than the 45-point national average. The study finds that a number of variables, including consistent homework completion, parental academic support, economic status, and assertiveness in the classroom, are associated with students’ academic achievement. These findings have implications for policy and action as well as a more comprehensive view of the opportunities and problems facing Nepal's school-level educational system. The study recommends that embarking upon a systemic, holistic approach devoted to identifying life skills, experiential learning, and inclusive practices. It also recommends to draw the expertise of school head teachers and parents to improve student outcomes.